2012
DOI: 10.1021/mp300408m
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Microbicide Nanoparticles with a Simulated Vaginal Fluid

Abstract: The interaction with cervicovaginal mucus presents the potential to impact the performance of drug nanocarriers. These systems must migrate through this biological fluid in order to deliver their drug payload to the underlying mucosal surface. We studied the ability of dapivirine-loaded polycaprolactone (PCL)-based nanoparticles (NPs) to interact with a simulated vaginal fluid (SVF) incorporating mucin. Different surface modifiers were used to produce NPs with either negative (poloxamer 338 NF and sodium laury… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
67
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(73 citation statements)
references
References 68 publications
6
67
0
Order By: Relevance
“…The aqueous fluid was modified from Owen & Katz [103] and contained 1.5% (w/v) pig gastric mucin type II, 0.5% (w/v) glucose, 0.351% (w/v) sodium chloride, 0.2% (w/v) lactic acid, 0.14% (w/v) potassium hydroxide, 0.1% (w/v) acetic acid, 0.04% (w/v) urea, 0.0222% (w/v) calcium hydroxide, 0.016% (w/v) glycerol and enough amount hydrochloride acid for pH 4.2. The artificial fluid did not change TEER up to at least 4 h and previous experiments demonstrated similar rheological behavior to native mucus [119]. Experiments using the described models showed that the presence of mucins had considerable impact in both the permeability and cell monolayer accumulation of dapivirine, either in suspension or associated to 170 nm PLGA nanoparticles (Fig.…”
Section: Supplementation Of Cell-based Mucosal Models With Artificialsupporting
confidence: 68%
See 2 more Smart Citations
“…The aqueous fluid was modified from Owen & Katz [103] and contained 1.5% (w/v) pig gastric mucin type II, 0.5% (w/v) glucose, 0.351% (w/v) sodium chloride, 0.2% (w/v) lactic acid, 0.14% (w/v) potassium hydroxide, 0.1% (w/v) acetic acid, 0.04% (w/v) urea, 0.0222% (w/v) calcium hydroxide, 0.016% (w/v) glycerol and enough amount hydrochloride acid for pH 4.2. The artificial fluid did not change TEER up to at least 4 h and previous experiments demonstrated similar rheological behavior to native mucus [119]. Experiments using the described models showed that the presence of mucins had considerable impact in both the permeability and cell monolayer accumulation of dapivirine, either in suspension or associated to 170 nm PLGA nanoparticles (Fig.…”
Section: Supplementation Of Cell-based Mucosal Models With Artificialsupporting
confidence: 68%
“…First, as previously reviewed by Griessinger et al, multiple techniques have been developed to study the mucus permeation or the mucus diffusion of DDS [117]. Transwell diffusion system (without cell seeding) [118] and multiple particle tracking [119] are mainly used. The second strategy is to add native or simulated vaginal fluid above the reconstructed multiplayer epithelium.…”
Section: Cervico-vaginal Tractmentioning
confidence: 99%
See 1 more Smart Citation
“…This in turn may potential- 78 ly increase protection against infection while allowing obtaining 79 coitally-independent microbicides. [8], respond to physiological changes occurring upon sexual inter-85 course (e.g., pH changes) [9], enhance drug targeting [10], promote 86 drug penetration and accumulation at genital tissues [11], increase 87 intracellular drug delivery [12], and improve drug activity [13]. 88 Further, drug-loaded polymeric nanoparticles (NPs) may benefi-89 cially affect local genital pharmacokinetics (PK) and, therefore, 90 potentially enhance the ability of antiretroviral compounds to pro-91 tect against infection in a coitally-independent fashion [14].…”
mentioning
confidence: 99%
“…Referred to the resistance to the environmental conditions, if the strains are going to be administered locally at the urogenital tract, they must be assayed in their resistance to vaginal fluid and/or urine [218,219]. If they will be applied as oral capsule or foods, their survival must be studied in intestinal fluid or into their components, either in one phase assays, or in continuous models resembling the different areas of the intestinal tract [220][221][222][223][224][225][226]..…”
Section: Accepted M Manuscriptmentioning
confidence: 99%